Closing the cycle of innovation in healthcare in Europe. (17th April 2020) - Hulstaert, Frank; Ruether, Alric; Demotes, Jacques; Melien, Øyvind
Abstract: Pragmatic or practice-oriented comparative effectiveness trials may be conducted to fill the evidence gaps that are revealed after the private sector has performed the trials needed for bringing their product to the market. A tool of increasing importance to identify such evidence gaps is resulting from health technology assessments (HTA) whereby the data derived from clinical research are examined in a systematic manner with reference to effect, safety, as well as additional parameters. Practice-oriented trials are informative for healthcare decision makers, practice-changing and may even be cost-saving for the healthcare payers. There are however only a limited number of funding sources for such trials. Public and private healthcare payers should stimulate the conduct of practice-oriented trials in their effort to maximize patient benefit within the limitation of the available resources. Pragmatic randomized trials can be performed at low cost when based on existing coded electronic health records and as well health registries. Public health decision makers are increasingly taking advantage of results from health technology assessments to support priority setting. In accordance with this it would appear reasonable that decision makers should get more involved in priority setting and funding also in the field of clinical research in order to provide further evidence needed for assessments, reassessments, and subsequent qualified decisions and resource allocations in health care. A closer dialogue and collaboration between the clinical research and HTA communities would facilitate a more efficient utilization of such opportunities.